Evaluation of the Impact of Backwater on the Hydraulics Performance of Modules using FLOW-3D - Che Wan Azman, Che Wan Nor Shahirah (Universiti Teknologi PETRONAS, 2020)
Bio-ecological swale with drainage module was the primary component of the Bio- Ecological Drainage Systems (BIOECODS) which provided flow attenuation by enabling natural filtration that had the potential to replace conventional channels in order to improve stormwater management in terms of quality and quantity. Backwater considerations were due to blockage, bends, soil porosity, module pattern and groundwater condition that tends to affect the output of hydraulic modules when completely installed on site that could cause ponding. The purpose of this study was to investigate the impact of backwater on the hydraulic performance by using simulation of FLOW-3D software in the free flow condition for control purpose and the flow parameters under the gate partially opened (GPO) with 2cm opening involving RAINSMART and REDAC modules.